Health system perspective of the role of DLH in strengthening household waste management: perception of a local environmental protection agency officers on open landfill systems - Purwati, Alvi; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: The final waste disposal management in Indonesia is still largely dominated by open landfills, despite the need to move away from this method. In a health systems framework, any players work in connected with others. The perception of local environmental protection officers (DLH) plays a crucial role in this persistence. Some officers believe landfills are necessary for waste management, making it hard to eliminate their use. This study explores the perspectives of DLH officers on waste management systems, focusing on their views about landfills and the importance of managing waste from the source. Methods: A total of 11 DLH officers were selected as informants in this study, providing information through direct interviews or via email. Data was collected between March and April 2023. Results: The findings indicate that while some DLH officers recognize the need for sustainable waste management practices, their ability to change the existing system is limited by their current understanding and education. Conclusion: It is essential to ensure that DLH officers have the appropriate educational background and a clear understanding of their responsibilities. This will enable them to implement sustainable waste management practices effectively and positively impact the environment.